An Analysis of Formal Language Style in The American President Movie - Shadrina, Shofya; Hellystia, Devi (JADEs Journal of Academia in English Education, 2023)
Language style serves as a supplementary instrument for individuals to partake in dialogue, drawing upon their speaking proficiency to align with the context and subject matter of the discourse. Using Martin Joss’s theory (1967), this research aims to find out the characteristics of formal language style that occur in the utterances in the American President movie. Descriptive qualitative method was used as the research design to analyze the characteristics of formal language style in the American President movie. The results of this research found 195 data which are presented in three points. The respectful tone (11), polite tone (21), avoid contraction of level grammar (22), avoid run-on sentence of level grammar (7), efficient words of level grammar (8), complete sentence of level grammar (113), and formal modal of level grammar (13). This means that the complete sentence of level grammar is prominently proved to be used in communication withing formal language style used in American President movie. based in the result of the research, it is fruitful to suggest the students of English Department to do further analysis about the five language styles used in other resources like movies, novels, or article that contain about the politics.